2013
DOI: 10.1074/jbc.m112.443671
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cystatin C in Amyloid Precursor Protein-induced Proliferation of Neural Stem/Progenitor Cells

Abstract: Background:The role of the amyloid precursor protein (APP) in neural stem/progenitor cell (NSPC) proliferation is poorly understood. Results: Immunodepletion of cystatin C from NSPC conditioned medium abrogated an effect of APP on NSPC proliferation. Conclusion: Cystatin C mediates APP-induced NSPC proliferation. Significance: The results increase understanding of mechanisms promoting NSPC survival and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 46 publications
1
34
1
Order By: Relevance
“…Furthermore, inhibition of ␣-secretase was reported to decrease NSPC proliferation, and soluble APP␣ was able to rescue this effect (24). However, our recent study showed that an APP-induced increase in NSPC proliferation was primarily due to the secretion of cystatin C rather than soluble APP␣ (19).…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Furthermore, inhibition of ␣-secretase was reported to decrease NSPC proliferation, and soluble APP␣ was able to rescue this effect (24). However, our recent study showed that an APP-induced increase in NSPC proliferation was primarily due to the secretion of cystatin C rather than soluble APP␣ (19).…”
mentioning
confidence: 90%
“…vious studies from our group (19) showed that NSPCs derived from APPKO mice proliferated less rapidly and differentiated into neurons less readily than NSPCs from WT mice. The effect on proliferation was found to be mediated by the secretion of cystatin C. Therefore, to examine the possibility that cystatin C might also influence NSPC differentiation, we first compared the neural differentiation levels of NSPCs derived from P0 WT and APPKO mice.…”
Section: Cystatin C Is Not Involved In Neuronal Differentiation-pre-mentioning
confidence: 99%
See 3 more Smart Citations